New piperidine-hydrazone derivatives: Synthesis, biological evaluations and molecular docking studies as AChE and BChE inhibitors - KAYMAKÇIOĞLU, BEDİA (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2016)
Hydrazones and the piperidine ring containing compounds were considered as beneficial substrates in drug design. Therefore, this study was aimed at the synthesis of new benzoyl hydrazones derived from ethyl 4-oxopiperidine-1-carboxylate and 2,6-diphenylpiperidin-4-one. The synthesized compounds (1-19) were screened for their antioxidant, anticholinesterase and anticancer activities. The antioxidant capacity of the compounds was evaluated by using four complementary tests. The results showed that compound 7 and 17 have the higher lipid peroxidation inhibitory activity than the other compounds. In DPPH scavenging assay, compounds 5, 6, 10,14, 17 demonstrated better activity than that of standard BHT, while in ABTS(+) scavenging assay compound 6 and 17 exhibited better activity among the other compounds. The CUPRAC assay disclosed that compound 2 displayed better activity than alpha-tocopherol. The anticholinesterase activity was performed against acetylcholinesterase (AChE) and butyrylcholinesterase.(BChE) enzymes. Compound 11 (IC50: 35.30 +/- 1.11 mu M) inhibited BChE better than galantamine (IC50: 46.03 0.14 mu M). We conclude that the compound 11 can be considered as a candidate for BChE inhibitor. Moreover docking method was applied to elucidate the AChE and BChE inhibitory mechanism of the compound 11. Molecular docking analysis revealed that compound 11 bound to BChE enzyme more efficiently when compared to the AChE due to its orientations and different types of interactions. In addition, the non-cytotoxic properties of the compounds brought them into prominence, although they did not show significant anticancer properties. (C) 2016 Elsevier Masson SAS. All rights reserved.
Keywords: Piperidine; Hydrazone; Anticholinesterase activity; Antioxidant activity; Molecular docking; ALZHEIMERS-DISEASE; ANTIOXIDANT ACTIVITY; MEDICINAL CHEMISTRY; ACETYLCHOLINESTERASE; DESIGN; POTENT; PROLIFERATION; GROWTH; ASSAY